Antiparkinsonian Effect of Nutmeg Ethanolic Extract (Myristica fragrans Houtt.) in Haloperidol-induced Mice - Palupi, Dwi Hadi Setya; Fekhayanti, Isma Galuh (Pharmaciana, 2024)
Parkinson's disease is a chronic neurological illness that may be caused by a decrease in dopaminergic neurons in the brain. Myristicin, eugenol, and flavonoids, which are bioactive compounds in nutmeg (Myristica fragrans Houtt.), may be able to treat Parkinson's disease. The goal of this study was to find out the antiparkinsonian effect of nutmeg in haloperidol-induced Parkinson's disease mice. Induction with haloperidol was carried out intraperitoneally for 7 consecutive days. Treatment with nutmeg uses three different doses (5, 10, and 20 mg/kg) for 7 days orally. Behavioral testing is carried out using the Rotarod test and the cylinder test. The results showed that nutmeg at a dose of 20 mg/kg was able to show significant improvement (P < 0.05) in the motor condition of test animals induced by haloperidol.